The Translation of Physics Texts by Western Missionaries During the Late Ming and Early Qing Dynasties and Its Enlightenment of Modern Chinese Physics - Yafeng Li; Jingmin Fu (Religions)
Christian culture is viewed as a translated cultural practice that has become intricately intertwined with the local culture over the course of historical development in China. Currently, many research findings focus on the translation of missionary religious texts during the late Ming and early Qing dynasties. However, the translation of non-religious texts by Western missionaries from the same period also plays a pivotal role in the development of Chinese society and culture. In order to verify the above point of view, this paper focuses on the translation of physics texts by Western missionaries during the late Ming and early Qing Dynasties. Examining the choice of physics texts translated by missionaries reveals the missionary motivations in evangelization. On the basis of analyzing the translation motivation, this study classifies the overall translation practice of Western missionaries in translating physical texts during that period, presenting the physical scientific knowledge brought to China at the time. Additionally, it explores how the translation of Western physical science enlightened the transformation and development of Chinese physics in modern times. Furthermore, the paper argues that the translations by Western missionaries played a crucial role in introducing new ideas and knowledge, contributing to the enlightenment of modern scientific knowledge in China, so as to underscore the value of the non-religious texts translated by Western missionaries to the society and culture in China.